FAKTOR-FAKTOR PENGHAMBAT PENGGUNAAN SEPEDA DI DAERAH GROGOL - Ricardo, Ricardo; Putranto, Leksmono Suryo (JMTS: Jurnal Mitra Teknik Sipil, 2024)
This research aims to explore the factors inhibiting the use of sustainable transportation, particularly bicycles, in the Grogol Region. In the context of sustainable urban development, transportation plays a crucial role, and bicycle use has been identified as a potential solution to reduce the negative impacts of conventional transportation. However, bicycle usage in many areas remains limited and faces complex barriers. This study will delve into factors such as bicycle infrastructure conditions, risk perceptions, travel distance, as well as the cultural and social norms that influence individual decisions to use bicycles. In the context of the Grogol Region, this case study will provide in-depth insights into the specific obstacles faced by bicycle users in this area. Additionally, this research will explore the social, economic, and environmental impacts of restricted bicycle usage. The results of this study are expected to contribute to the formulation of more effective policies to support bicycle use as an integral part of sustainable transportation systems. Penelitian ini bertujuan untuk menjelajahi faktor-faktor yang menghambat penggunaan transportasi berkelanjutan, khususnya penggunaan sepeda, di Daerah Grogol. Dalam konteks pembangunan perkotaan yang berkelanjutan, transportasi berperan penting, dan penggunaan sepeda telah diidentifikasi sebagai salah satu solusi yang berpotensi mengurangi dampak negatif transportasi konvensional. Namun, penggunaan sepeda di banyak daerah masih terbatas dan menghadapi hambatan yang kompleks. Penelitian ini akan menggali faktor-faktor seperti kondisi infrastruktur jalur sepeda, persepsi risiko, jarak perjalanan, serta pengaruh budaya dan norma sosial yang mempengaruhi keputusan individu untuk menggunakan sepeda. Dalam konteks Daerah Grogol, kajian kasus ini akan memberikan wawasan mendalam tentang hambatan yang khusus dialami pengguna sepeda di wilayah ini. Penelitian ini juga akan mengeksplorasi dampak sosial, ekonomi, dan lingkungan dari penggunaan sepeda yang terhambat. Hasil dari penelitian ini diharapkan akan memberikan kontribusi untuk merumuskan kebijakan yang lebih efektif dalam mendukung penggunaan sepeda sebagai bagian integral dari sistem transportasi berkelanjutan.